(3JMUjd GdfLGIs - (3eMeO Hf LeGd GdOjf Hf MSf Hf GdeWgQs
(3ChdgG (B:s
(3GdMeO ddg hGLH GdhLhO dPGJg CeG HYO agPG cJGH JMUjd GdfLGI ai CUhd GdOjf s
(3BNQgG (B:s
(3GdeHMK GdKGfi YTQ ai GdCeQ HGdeYQha HGdeYQha hGdfgi Yf GdefcQ gPG BNQ eG fPcQg ai gPg GdQSGdI hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3cJH fgGjI GdeNWhW HNW eZGjQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(1771) s
Keywords: (3GdJhMjO hGdedd hGdfMds